Diurnal raptors at rescue centres in the Czech Republic: Reasons for admission, outcomes, and length of stay - Kadlecova, Gabriela; Voslarova, Eva; Vecerek, Vladimir (PloS one, 2022)
Rescue centres play an important role in the protection of raptors living in the wild by caring for injured or debilitated animals and abandoned young with the aim of returning them to the wild. A total of 22,538 raptors were admitted to 34 rescue centres in the Czech Republic in the years 2010-2019, with an increasing trend during the monitored period (rSp = 0.7333, p < 0.05). The most frequent reasons for their admission were other injuries and fractures (26.52%), the admission of young (22.98%), and the admission of raptors injured by electric shock injuries (20.51%). It proved possible to release 42.45% of admitted raptors back into the wild, the majority of which (91.05%) were released using the hard-release method. Foster parents were used in 1% of cases and a replacement nest in 0.2% of cases involving the rearing of young. In spite of all the care provided at rescue centres, a total of 39.97% of raptors admitted either died or had to be euthanized. Among them, most raptors were euthanized or died due to injuries caused by collision with a vehicle, electric shock injuries, and other injuries. This generally occurred shortly after admission (a median of two days). The importance of the work of rescue centres lies not merely in returning injured raptors back into the wild (which proves possible in around half of all cases), but also in obtaining information about the factors endangering raptors in the wild and contributing toward a decline in their populations. The findings provide information about human-wildlife interactions in the Czech Republic and their implications for conservation as well as on the effectiveness of rescue centres to successfully treat and subsequently release raptors back into the wild.
Keywords: poranění elektrickým proudem; Animals; Hospitalization; divoká zvířata; Raptors; hospitalizace; zvířata; nemoci ptáků; Humans; Animals, Wild; dravci; Electric Injuries; Bird Diseases; Czech Republic; lidé; Length of Stay; délka pobytu; Česká republika